Supplement With Calcium or Alendronate Suppresses Osteopenia Due to Long Term Rabeprazole Treatment in Female Mice: Influence on Bone TRAP and Osteopontin Levels - Shaalan, Aly A.M.; El-Sherbiny, Mohamed; El-Abaseri, Taghrid B.; Shoaeir, Mohamed Z.; Abdel-Aziz, Tarek M.; Mohamed, Magda I.; Zaitone, Sawsan A.; Mohammad, Hala M. F. (Frontiers in Pharmacology, 2020)
Background and purpose: Rabeprazole, a proton pump inhibitor (PPIs) is much endorsed to patients with increased gastric acidity. PPIs were accused to have osteoporotic effects on patients who chronically use them. The point of the current investigation was to decide the impact of rabeprazole on osteoporosis and to explore the modulatory effects of dietary calcium or alendronate on this side effect. Methods: 80 female mice were alienated into 4 groups maintained for 18 weeks: [1] Vehicle group: given distilled water in 12 ml/kg, P.O. [2] Rabeprazole control group: given rabeprazole in a dose equals 10-mg/kg every 48 h, P.O. [3] Rabeprazole+calcium: given rabeprazole (10-mg/kg every 48 h) along with calcium supplement. [4] Rabeprazole+alendronate: given rabeprazole (10-mg/kg every 48 h) and alendronate (1-mg/kg per week, i.p.). Serum calcium, phosphorus and parathyroid hormone were measured. Both femurs are kept in paraformaldehyde, and then the right one was used for X-ray examination with analysis by Digora software and the left one for histopathological examination (H&E) and immunohistochemical stains for osteopontin and tartrate resistant acid phosphatase (TRAP). Results: Calcium supplementation or administration of alendronate along with rabeprazole significantly restored the mean bone density as shown by X-ray analysis. Femurs from mice received rabeprazole showed widely separated, thin-walled bone trabeculae and increased number of osteoclasts. Calcium or alendronate with rabeprazole showed thick bone trabeculae without full recovery from rabeprazole induced damage. Adding calcium supplementation to rabeprazole did not affect the histological abnormalities related to osteoclasts meanwhile alendronate produced inactivation of osteoclasts. Both calcium and alendronate decreased the rabeprazole-induced increment in the femur osteopontin level. Conclusion: Calcium or alendronate can be recommended for female patients on PPI therapy who are at risk of osteopenia.